THE PRESERVATION AND REVITALIZATION OF LOCAL ETHNIC MUSIC CULTURE IN SCHOOL MUSIC EDUCATION PHILOSOPHICAL IDENTITY AND CULTURAL HERITAGE - Zhang, Guozhong (European journal for philosophy of religion, 2024)
The development of local ethnic music culture is affected by the impact of foreign music culture, the establishment of the teaching system of music culture knowledge, understanding of history, culture, social background to mobilise the sensory mechanism, based on the popular elements of ethnic music innovation, as well as enrichment of the regional ethnic music and cultural activities, and active promotion of the protection of the local ethnic music culture of the five factors. The five factors relationship value are 0.440, 0.517, 0.541, 0.498 are all greater than 0, and there is a significant relationship between the factors. The path coefficients of the refinement factors on the protection of local ethnic music culture are all greater than 0, and p=0.000<0.001, with high significance. 4 factors, namely, the construction of teaching system, mobilisation of the sensory mechanism, ethnic music innovation, and music cultural activities, have a significant positive relationship on the protection of local ethnic music culture. School music education should construct the teaching system, mobilise students' senses and thinking, use new media communication platforms, and carry out regular thematic activities, so as to promote better protection and revitalisation of local ethnic music culture and advance the development of music and cultural diversity.